1996
DOI: 10.1177/000331979604700510
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Ended-Pattern Coronary Circulation: Demonstration of Its Potential "Self-Cure" Role in Obstructive Coronary Artery Disease

Abstract: A case of open-ended-pattern coronary circulation that protected the left ventricle when one large vessel was occluded is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Among 20,880 coronary angiographies the past 9 years this is the second case, reported from our Interventional Unit, concerning intercoronary communication between LAD and RCA with 100% stenosis of main coronary artery (RCA), and no evidence of myocardial infarction [22]. Its role seems to be benign and potentially cardioprotective against the course of atherosclerotic coronary artery disease.…”
Section: Discussionmentioning
confidence: 88%
“…Among 20,880 coronary angiographies the past 9 years this is the second case, reported from our Interventional Unit, concerning intercoronary communication between LAD and RCA with 100% stenosis of main coronary artery (RCA), and no evidence of myocardial infarction [22]. Its role seems to be benign and potentially cardioprotective against the course of atherosclerotic coronary artery disease.…”
Section: Discussionmentioning
confidence: 88%
“…There were only two cases in the literature similar to our case. Antonellis et al and Gavrielatos et al reported intercoronary communications between LAD and RCA with total occlusion of the RCA and no evidence of myocardial infarction and they speculated that even thought open ended circulation pattern prevented myocardial necrosis and preserved cardiac contractility, was not sufficient enough to avert angina (10,11). However, Donaldson and Isner reported a case with >95% stenosis of the RCA with a LAD-posterior descending artery continuity and evidence of extensive transmural myocardial infarction in the distribution of the posterior descending artery (12).…”
Section: Discussionmentioning
confidence: 99%